Clinicopathological study of sinonasal masses - Humayun, Abu HenaMohammad Parvez; Huq, AHM Zahurul; Ahmed, SM Tarequddin; Kamal, Md Shah; U, Kyaw Khin; Bhattacharjee, Nilakanta (Bangladesh Journal of Otorhinolaryngology, 2010)
Objective: To observe the incidence, clinical presentation and to perform comparative study of different sinonasal masses. Study design: Prospective study. Setting: Department of otolaryngology and Head-Neck Surgery & ENT OPD of Chittagong Medical College Hospital. Patients & methods: 50 patients are included in this study (39 male & 11 female) between the ages of 3 years and 80 years who were treated between August 2006 to January 2007. Study based on history, clinical, radiological, laboratory and histopathological examination. Results: Mean age for male was 35.12 years and for female was 22.63 years. Male to female ratio was 3.5:1. Highest frequency was noted in second decade. Most of patient (78%) were from poor class. Frequency of inflammatory nasal masses were more in second decade, benign tumour in fourth and fifth decade, malignant tumour in second decade (OAN & NHL) and fifth and second decades (others). Rhinosporidiosis were most frequent inflammatory nasal masses. Nasal obstruction was the commonest and orbitus symptoms were less frequent symptoms. But orbital symptoms were more prevalent in malignant lesion. Conclusion: sinonasal masses are found in all age group. Rhinosporidiosis are appearing to be the commonest nasal masses. The prevalence of nasal polyp is also high. Among the malignant sinonasal masses the percentage of squamous cell carcinoma is high. DOI: 10.3329/bjo.v16i1.5776 Bangladesh J Otorhinolaryngol 2010; 16(1): 15-22